Penyelesaian Sengketa Waris Akibat Surat Wasiat Tertulis Yang Memberikan Hak Waris Kepada Selain Ahli Waris - Nada Syifa Nurulhuda; Muhammad Dewanto Adi Saputra; Agus Mahardika; Muhammad Rizki; Dwi Aryanti Ramadhani; Laily Maghfiroh (Indonesian Journal Publisher, 2024)
This research focuses on the resolution of inheritance disputes arising from wills that allocate assets to individuals other than the legal heirs. Using a normative juridical method with a conceptual approach, the study refers to provisions in the Civil Code and the Judicial Power Law. The study highlights the significant legal force of wills, which can override statutory inheritance rights if they comply with formal and material requirements. Emphasizing the necessity of thorough judicial consideration in dispute resolution, the research aims to ensure fair decisions that do not harm any party by adhering to authentic evidence and applicable legal provisions. An examination of Case Number 307/PDT.G/2021/PN JKT.SEL illustrates how an executor of a will, even if not a legal heir, can be legally recognized if appointed in a formally and materially compliant will. The results indicate that such executors can indeed be acknowledged, reinforcing the importance of the testator's intentions and legal certainty in inheritance division. The study concludes that while wills can legally appoint non-heirs as executors, ensuring compliance with legal procedures is crucial for upholding the testator’s wishes and maintaining fairness in inheritance disputes.